The princess spy - Dickerson, Melanie (Dickerson, Melanie. Hagenheim series., 2014)
The year is 1413. Margaretha hopes her newest suitor, Lord Claybrook, will be her one true love, but when an injured man is brought to Hagenheim Castle claiming to be an English lord who was attacked by Claybrook, Margaretha is drawn into a plot, not knowing who is telling the truth.